Analisis Keuntungan Usaha Keripik Pisang “Nur Hayati” Di Desa Kinali Kecamatan Kawangkoan Kabupaten Minahasa - Arsyad, Eka Vanisa; Pakasi, Caroline Betsi Diana; Rori, Yolanda Pinky Ivanna (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the profit of Nur Hayati's banana chip business in Kinali Village, Kawangkoan District, Minahasa Regency. The data analysis method was carried out using descriptive analysis method and presented in tabular form, then measured by the Revenue Cost Analysis (R/C) formula. The data collection method in this study was carried out by collecting primary data and secondary data. Primary data were obtained through interviews with the parties concerned based on a list of questions (questionnaires) that had been prepared, as well as direct field observations. Meanwhile, secondary data was obtained via the internet using Google Scholar. The results of this study show that Nur Hayati's banana chip business has a profit of Rp. 27,600,000 every month and is supported by an R/C Ratio value of 4.7, which means that Nur Hayati's banana chip business is experiencing big profits because the R/C Ratio value is > 1.